Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5152/tpd.2013.3191
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Intestinal Parasites in Children with Helicobacter pylori Gastritis Evaluated Retrospectively

Abstract: ÖZET Amaç: Gelişmekte olan ülkelerde H. pylori enfeksiyonu gelişmiş ülkelere göre daha sık ve daha erken yaşta görülmektedir. Etyopatogenezinde kalabalık ailelerde yaşam, annenin eğitim seviyesinin düşük olması, düşük ekonomik gelir, kirli içme suları gibi faktörlerin varlığında daha sık görüldüğü bildirilmiştir. Sosyoekonomik durumu iyi olmayan bölgelerde intestinal parazitozların da daha sık görüldüğü bilinmektedir. Bu çalışmada amaç, H. pylori gastriti olduğu endoskopik ve histopatolojik olarak ispatlanmış … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
1
3
Order By: Relevance
“…Our result are not in line with the findings of Gökşen et al (2016) who reported 14.8% for G. lamblia in the H. pylori -positive group, which was in agreement with Escobar-Pardo et al (2011) who also found a significant association between H. pylori and G. lamblia . However, our conclusion was in total disagreement with the finding of Uğraş & Miman (2014) , who reported no significant association between H. pylori and intestinal parasites in Turkey. This may be due to differences in the study areas with different food and life style of individuals.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result are not in line with the findings of Gökşen et al (2016) who reported 14.8% for G. lamblia in the H. pylori -positive group, which was in agreement with Escobar-Pardo et al (2011) who also found a significant association between H. pylori and G. lamblia . However, our conclusion was in total disagreement with the finding of Uğraş & Miman (2014) , who reported no significant association between H. pylori and intestinal parasites in Turkey. This may be due to differences in the study areas with different food and life style of individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…As far as the control group is concerned, the overall occurrence rate reported was 10%. This rate is lower than the rate among H. pylori patients and higher than the rate reported by Uğraş & Miman (2014) . The difference in rates between the control group and patient with H. pylori was significant.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In previous study in Turkey, lower occurrence rate of 7.61% was reported by Ugras and Miman [32]. The findings were not statistically significant (p>0.05).…”
mentioning
confidence: 57%